Modelo de Thirring com simetria de Gauge: uma análise funcional - Bufalo, Rodrigo Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
We study the quantum field theory in (1 + 1)-dimensional space-time in exactly solvable models via the functional integral formalism. The Hamiltonian structure of the models is studied following the Dirac's procedure for constrained systems and the generating functional for the Green's functions is implemented into the functional integral technique. Also, we implement the Schwinger-Dyson equations and the Ward- Takahashi identities. We made emphasize in the gauge structure of Gauged Thirring Model and study the strong limits of their coupling constants

Realizamos um estudo da Teoria Quântica de Campos num espaço-tempo de (1 + 1)-dimensões em modelos exatamente solúveis via o formalismo de integração funcional; em que a estrutura Hamiltoniana dos modelos é construída segundo a abordagem de Dirac para sistemas vinculados. Além disso, implementamos as equações de Schwinger-Dyson e as identidades de Ward-Takahashi. Damos ênfase na estrutura de gauge do modelo de Thirring com simetria de gauge e analisamos os limites fortes das suas constantes de acoplamento
Keywords: Teoria quântica de campos; Análise funcional; Quantum field theory